Determinan Produktivitas dan penyerapan Tenaga Kerja Pada Industri Perak di Kabupaten Klungkung - Duwi Antari, Anak Agung Istri Indra; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 9, September 2016 (pp. 902 - 1010), 2016)
The purpose of this study was to analyze the influence of capital, raw materials and wage data on labor productivity in the silver industry in Klungkung regency. This research was conducted in Kamasan village which has a number of craftsmen silver 224 business units. The sample in this study amounted to 69 respondents. The method used in this study include observation, questionnaires and structured interviews. This study using a test path and Sobel test to determine the direct and indirect relationships between variables. The result showed that the capital, raw materials and wage levels and significant positive effect on labor productivity of industrial silver. Capital, raw materials, wages and labor productivity and a significant positive effect on employment silver industry. Capital, raw materials, wages indirect effect on the absorption of labor through labor productivity, but labor productivity is not an intervening variables that mediate the variable capital, raw materials and wage increases on employment in the silver industry in the village of Kamasan
Keywords: silver industry; capital; raw materials; wages; productivity; employment.